Learning Reading The Beginning Using Educative Game Media Learning Reading Current Android Versions - Afiyati, Fifi Sri Ratu; Iswara, Prana Dwija (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Reading individual abilities must be possessed. A child can read and understand the contents of the reading begins with the beginning of learning to read. Given the importance of learning to begin with reading, every teacher must be able to teach beginning reading in a systematic, effective, easy and fun way. As technology develops, the demands of the times are also higher. Teachers should be able to present learning by using learning media in accordance with the times. Through the educational game media learning to read fluently in the android version, beginning reading can be a systematic, effective, easy and fun learning. The results of observations at an elementary school in Bekasi, from 28 students of class II, there were 5 students who were not able to read the beginning well. After being given treatment using the educational game media learning to read fluently, the observations showed that the students looked enthusiastic and cheerful when carrying out the learning. Based on the results of the interviews, the five students stated that learning to read felt easy and fun. The reading test results show the post-test results improved significantly compared to the pre-test results